Rancang Bangun Pengusir Hama Padi Berbasis Node MCU dengan Solar Cell - Sihotang, Willy Hardiansyah; Purba, Dharma Putra; Togar Timoteus Gultom; Despaleri Perangin (Lembaga Pengembangan Kinerja Dosen, 2025)
Pests are a major challenge for rice farmers because they can reduce the quality of the harvest. Manual pest control which is still widely used tends to be less effective and requires large costs and energy. With the advancement of technology, there is a more effective innovative solution, namely Node MCU-based devices that utilize renewable energy, such as solar cells. This device is able to repel pests automatically and is environmentally friendly, making it a more modern and sustainable alternative. This study aims to design a Node MCU-based rice pest repellent system with energy from solar cells. The results of this study showed that the tool ran smoothly, indicated by the absence of errors when turning on the tool, and had 2 failures during the command execution process from 20 tool trials, therefore the percentage of resistance to malfunction of 90% was obtained from the number of failed trials multiplied by 100, and the results multiplied by the total number of trials. It can be concluded that the tool functioned normally during the trial in the rice field area.